2021
DOI: 10.3390/ijerph18052579
|View full text |Cite
|
Sign up to set email alerts
|

Do Financial Literacy and Financial Education Influence Smoking Behavior in the United States?

Abstract: Smoking is still a serious economic, health, and social problem despite various efforts to curb its prevalence. We examined the influence of financial literacy and financial education on the smoking behavior in the United States in terms of the use of rational decision-making abilities to reduce irrational behavior. We hypothesized that financial literacy and financial education, as proxies for rational decision making, would reduce the likelihood of smoking. We used data from the Preference Parameters Study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 98 publications
6
27
1
4
Order By: Relevance
“…The government should also introduce financial literacy improvement policies, as we found that people with better financial literacy were less likely to have vaccine hesitancy. This finding is consistent with other studies reporting that financial literacy discourages irrational behaviors [ 49 , 50 , 51 ] and is positively associated with health literacy [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The government should also introduce financial literacy improvement policies, as we found that people with better financial literacy were less likely to have vaccine hesitancy. This finding is consistent with other studies reporting that financial literacy discourages irrational behaviors [ 49 , 50 , 51 ] and is positively associated with health literacy [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…For the explanatory variables, we included gender, age, education, place of residence, marital status, children in the household, living situation, employment status, household income, and household assets as demographic variables. We also included financial literacy as a proxy for rational decision-making ability in health-related behaviors, as suggested by [ 47 , 48 , 49 , 50 , 51 ]. Furthermore, we included subjective health status, future anxiety, risk preference, and myopic view of the future.…”
Section: Methodsmentioning
confidence: 99%
“…We argue that financially literate people or those with good investment knowledge will invest in health by exercising regularly. The findings emphasize the role of financial literacy in improving peoples' rational decision-making capacity, as in previous studies [23,33,34,37,39,96]. Moreover, our study shows that respondents who are males, middle-aged, have smaller household size, have higher balance of financial assets, are not current smokers, current drinkers, and are currently happy are more likely to exercise regularly.…”
Section: Discussionsupporting
confidence: 86%
“…Respondents' psychological characteristics show that they are moderately myopic about the future (Mean = 2.58, SD = 1.01), moderately satisfied with their current financial condition (Mean = 2.70, SD = 1.10), are anxious about their life in old age (Mean = 3.72, SD = 1.18), are careful buyers (Mean = 4.0414, SD = 0.9854), have a moderate level of trust in others (Mean = 2.81, SD = 0.95), and are moderately lonely (Mean = 2.87, SD = 1.19). The demographic, socio-economic, and psychological characteristics of respondents are consistent with previous studies (Kadoya et al, 2021;Khan et al, 2021;Ono et al, 2021;Watanapongvanich et al, 2021). Table 3 presents a detailed description of special financial frauds such as fictitious billing fraud, loan guarantee fraud, and refund fraud based on important demographic, socioeconomic, and psychological variables.…”
Section: Descriptive Statisticssupporting
confidence: 74%